2017
DOI: 10.1080/02670836.2017.1302141
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pulsed magnetic treatment on the corrosion of titanium

Abstract: This is an Accepted Manuscript of an article published by Taylor & Francis in Materials Science and Technology on 17 March 2017, available online: http://www.tandfonline.com/doi/full/10.1080/02670836.2017.1302141. Under embargo. Embargo end date: 17 March 2018.Results of corrosion tests of titanium in the initial state and after treatment using pulsed magnetic field are presented. It is shown that samples after treatment have better corrosion resistance due to the formation of denser and finer corrosion produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…A uniform pattern of dislocations similar to that presented in Figure 9 has also been observed for steel and titanium as a result of magnetic field treatment in earlier research [47,48]. Ma et al [49] reported an increase in the number of dislocations in steel as a result of magnetic treatment; this was attributed to a "magneto-stress" which acted on the dislocations and activated Frank-Read sources and dislocation slip increasing the dislocation density.…”
Section: Effect Of Electric Current and Magnetic Field On Dislocations Rearrangement And Precipitationsupporting
confidence: 74%
See 1 more Smart Citation
“…A uniform pattern of dislocations similar to that presented in Figure 9 has also been observed for steel and titanium as a result of magnetic field treatment in earlier research [47,48]. Ma et al [49] reported an increase in the number of dislocations in steel as a result of magnetic treatment; this was attributed to a "magneto-stress" which acted on the dislocations and activated Frank-Read sources and dislocation slip increasing the dislocation density.…”
Section: Effect Of Electric Current and Magnetic Field On Dislocations Rearrangement And Precipitationsupporting
confidence: 74%
“…From these equations ( 4), the kinetic energy of the electron drift by the action of the electric field under an isotropic scattering of electrons can be derived [47] as…”
Section: Effect Of Electric Current and Magnetic Field On Dislocations Rearrangement And Precipitationmentioning
confidence: 99%
“…The electroplastic effect can be promoted by the electron wind force that can lead to dislocation motion. This effect of the electric pulse current on the crystal lattice of a metal can be estimated using the following basic relations that determine the kinetics of the interaction of conduction electrons with the crystal lattice in accordance with existing concepts of electrical conductivity [24,25] :…”
Section: Resultsmentioning
confidence: 99%
“…This potential has been demonstrated also in alloy manufacture. Babutskyi et al presented the effect of magnetic pulses on Ti-alloys [15]. The evolution of structure and properties of pearlitic steels under long-term mechanical loading has been reported by Gromov et al [16].…”
Section: Manufacture Of Materials Using External Fieldsmentioning
confidence: 99%